2020
DOI: 10.1016/j.avsg.2020.01.102
|View full text |Cite
|
Sign up to set email alerts
|

Occlusion of the Celiac Artery during Endovascular Thoracoabdominal Aortic Aneurysm Repair Is associated with Increased Perioperative Morbidity and Mortality

Abstract: Background: Some studies suggest that celiac artery coverage during elective endovascular thoracoabdominal aortic aneurysm (TAAA) repair is safe given sufficient collateralization of visceral organ perfusion from the superior mesenteric artery. However, there is concern that celiac artery coverage may lead to increased risk of foregut or spinal cord ischemia with an attendant increased risk of mortality. We sought to investigate rates of bowel ischemia, spinal cord ischemia, and 30-day mortality associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…4,13,26 Diverging data exist in the study of King et al who examined the effect of CAO versus CA preservation on mortality, spinal cord ischemia, and bowel ischemia in patients obtaining endovascular repair for TAAA, using data obtained through the Society for Vascular Surgery Vascular Quality Initiative (SVS-VQI). 10 The authors identified a total of 628 cases treated with EG, 44 patients among them (7% of the population) having inadvertent or intentional CAO and the remaining receiving CA revascularization. Their results showed that CAO was associated with higher 30-day mortality compared with patients with CA revascularization (11% vs 4%, respectively) and higher incidence of bowel ischemia (9% vs 2%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4,13,26 Diverging data exist in the study of King et al who examined the effect of CAO versus CA preservation on mortality, spinal cord ischemia, and bowel ischemia in patients obtaining endovascular repair for TAAA, using data obtained through the Society for Vascular Surgery Vascular Quality Initiative (SVS-VQI). 10 The authors identified a total of 628 cases treated with EG, 44 patients among them (7% of the population) having inadvertent or intentional CAO and the remaining receiving CA revascularization. Their results showed that CAO was associated with higher 30-day mortality compared with patients with CA revascularization (11% vs 4%, respectively) and higher incidence of bowel ischemia (9% vs 2%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The difference in their results which is in the higher range of the rates of similarly reported studies 9,13,18 could be attributed to the fact that there was lack of data regarding the preoperative imaging on establishing mesenteric circulation and the assessment of sufficient celiac collateralization in patients treated with CAO, thus not enabling the proper selection of "fit" patients for CAO. 10 The technique of CAO seems safe; however, its prognostic success was largely associated with 2 principal interconnected conditions. The first is the anatomical pattern of the splanchnic circulation, and the second is the preoperative demonstration of adequate collateral circulation between the celiac and SMA, which is crucial prior to considering intentional coverage of the CA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations